The electrochemical measurements investigation of NiCo2O4 for electrode materials of energy storage devices by using digital holography technique - Tawipon Prakobsang; Worawee Saei; Thee Kongsubto; Chesta Ruttanapun; Prathan Buranasiri; Suwan Plaipichit; Pattareeya Damrongsak; Chaval Sriwong (My University, 2021)
The electrochemical properties of NiCo2O4 for using as electrode materials for the potential applications have been investigated by electrochemical measurement which composed of cyclic voltammetry (CV) and galvanostatic chargedischarge (GCD). These processes are generating the ion exchange between the electrode and electrolyte, wherein induce the surface change of the interface. Especially, since in the cycle ability measurement using the potentiostat needed to repeat the cycle into the electrode for many times, the effective of the electrode is reduced. In this research, digital holographic technique was used to investigate the different properties of interface of the NiCo2O4 electrode while operating under the various electrochemical techniques. In our DH recording, the surface change of the electrode was expose at the difference potential scan rate at 1, 5, 10, 50, 100 and 200 mV/s of CV, and the difference current densities at 1, 2, 3, 5, 10 and 20 A/g of GCD and vary times of cycle ability test every 50 cycle times to 1000 cycles. In the end the reconstructed DH images of the electrode have been used to analyze the results from electrochemical measurement.
Keywords: Photovoltaic System Optimization Techniques; Electrowetting and Microfluidic Technologies; Transition Metal Oxide Nanomaterials